2018
DOI: 10.1080/00380253.2018.1479202
|View full text |Cite
|
Sign up to set email alerts
|

Race, Xenophobia, and Punitiveness Among the American Public

Abstract: We outline four connections between xenophobia and punitiveness toward criminals in a national sample of Americans. First, among self-identified whites xenophobia is more predictive of punitiveness than specific forms of racial animus. Second, xenophobia and punitiveness are strongly connected among whites, but are only moderately and weakly related among black and Hispanic Americans, respectively. Third, among whites substantial proportions of the variance between sociodemographic, political, and religious pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
0
19
2
1
Order By: Relevance
“…In addition, many studies have shown that racial resentment, especially among Whites, is predictive of support for various social control measures, including increased criminal justice spending (Barkan & Cohn, 2005; Hurwitz & Peffley, 2005), harsher criminal sentencing and the death penalty (Cohn, Barkan, & Halteman, 1991; Johnson, 2001; Soss, Langbein, & Metelko, 2003), “get tough” forms of juvenile justice (Pickett & Chiricos, 2012; Pickett, Chiricos, & Gertz, 2014), and other punitive criminal justice policies (Peffley & Hurwitz, 1998, 2002). These linkages between threat-related attitudes and punitiveness have been shown to be closely related to other sentiments, including racialized conceptions of crime, resentment stemming from economic competition with minority groups, perceptions that minority groups receive “special treatment” through government social welfare programs, and general feelings of anger or bitterness toward minorities (Baker, Cañarte, & Day, 2018; Chiricos et al, 2004; King & Wheelock, 2007; Unnever & Cullen, 2010a, 2012).…”
Section: Prior Research On Out-group Animus and Punitivenessmentioning
confidence: 99%
“…In addition, many studies have shown that racial resentment, especially among Whites, is predictive of support for various social control measures, including increased criminal justice spending (Barkan & Cohn, 2005; Hurwitz & Peffley, 2005), harsher criminal sentencing and the death penalty (Cohn, Barkan, & Halteman, 1991; Johnson, 2001; Soss, Langbein, & Metelko, 2003), “get tough” forms of juvenile justice (Pickett & Chiricos, 2012; Pickett, Chiricos, & Gertz, 2014), and other punitive criminal justice policies (Peffley & Hurwitz, 1998, 2002). These linkages between threat-related attitudes and punitiveness have been shown to be closely related to other sentiments, including racialized conceptions of crime, resentment stemming from economic competition with minority groups, perceptions that minority groups receive “special treatment” through government social welfare programs, and general feelings of anger or bitterness toward minorities (Baker, Cañarte, & Day, 2018; Chiricos et al, 2004; King & Wheelock, 2007; Unnever & Cullen, 2010a, 2012).…”
Section: Prior Research On Out-group Animus and Punitivenessmentioning
confidence: 99%
“…The specific indicators used were: "Immigrants are more likely to commit crime than U.S. citizens"; "Recent immigrants are more reluctant to assimilate than previous immigrants"; "Immigrants are a drain on the economy"; "Immigrants bring diseases to the United States"; "Police should be allowed to raid businesses and homes in order to find undocumented workers"; "Deportation is a good solution to immigration issues"; and "Creating a 'pathway to citizenship' will encourage illegal immigration." These items were developed by the CSAF research team based on previous measures of xenophobia in conjunction with content analyses of news stories about immigrants in the U.S. used to identify key issues and discourse (Baker, Cañarte, and Day 2018). The battery attempts to capture multiple dimensions of perceived threat shown to be important cross-cultural components of xenophobia-including economic, medical, cultural, and criminal-tailored to samples from the U.S.…”
Section: Xenophobiamentioning
confidence: 99%
“…Altemeyer (2003) argues that this association is driven by early-life socialization emphasizing religious ethnocentrism which fosters other prejudices throughout life. Out-group prejudice may have important implications for punitive attitudes among the religious; for example, Baker et al (2018) found that, among White Americans, xenophobia partially mediated the association between religious fundamentalism and punitiveness. In terms of crime perception, xenophobic attitudes among the religious may fuel the belief that immigrants 'bring crime' to the United States, resulting in heightened punitiveness driven by out-group hostility.…”
Section: Religion Fear Of Crime and Xenophobiamentioning
confidence: 99%